Mesin Penyiram Tanaman Otomatis Berbasis Panel Surya untuk Budidaya Tanaman Kangkung di Kel. Mulyorejo, Malang - Bambang Minto Basuki; Abdul Muta’ali (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This community service activity is aimed at helping women's farmer groups in Mulyorejo Village, Malang, in developing automatic watering technology based on renewable energy for water spinach cultivation. The system developed uses solar panels as an energy source, which drives the automatic watering machine. This technology is expected to increase irrigation efficiency, reduce dependence on human labor, and increase the productivity of water spinach plants. The results of the activity show that the use of this automatic watering machine can reduce operational costs and improve plant quality.